APLIKASI ANAGLYPH 3D TATA CARA SHOLAT DAN DOA BERBASIS LIGHT VIRTUAL REALITY - Ahmad Muammar Lubis; Sumi Khairani; Rismayanti (Jurnal Ilmu Komputer dan Sistem Informasi, 2024)
Prayer is the second pillar of Islam and it is the pillar that is emphasized most after the two sentences of the shahada. Prayer is the connection between a servant and his Lord. Prayers are of two types, namely prayers of worship and prayers of supplication. Allah's closeness to His servants is divided into two types, namely; the closeness of His knowledge to every creature and the closeness to His servants in giving them every request, help and taufik. Learning prayer movements and prayers should be taught from an early age (children). Guidance from parents and teachers is the most important way to provide learning media. So far, conventional learning in the form of books makes children bored, so creativity or interactive learning methods are needed, one of which is multimedia-based learning.